Effect of appropriate dose, spectrum, and timing of antibiotics on 28-day mortality in patients with sepsis in the emergency department - Pitsucha Sanguanwit (2022)
Background: Appropriate antibiotics prescribing is key to treatment and to preventing mortality in patients with sepsis. The aim of this study was to determine the effect of the appropriate timing, spectrum, and dose of antibiotics on 28-day mortality in patients with sepsis. Methods: We performed a retrospective cohort observational study. We enrolled patients with sepsis in the emergency department of a tertiary care hospital between 1 March and 31 July 2019. Patients were coded into an appropriate antibiotics group (time, spectrum, dose) and an inappropriate antibiotics group. We collected information of patient characteristics, comorbidities, vital signs, laboratory test results, and initial treatment. We followed patient outcomes, 28-day mortality, hospital deaths, 28-day ventilator-free days, and 28-day hospital-free days. Results: A total of 593 patients were enrolled, with 323 (54.46%) in the appropriate antibiotics group. We used multivariate logistic analyses to assess factors for mortality. Primary outcomes of appropriate antibiotics (administration within 60 min of triage, appropriate spectrum and dose) did not affect 28-day mortality (adjusted odds ratio [OR], 0.57; 95% confidence interval [CI] 0.22–1.144; P=0.23). Subgroup analysis showed that appropriate spectrum alone influenced 28-day mortality (adjusted OR, 0.38; 95% CI, 0.15–0.99; P=0.047). Appropriate antibiotics was not associated with in-hospital mortality (adjusted OR, 0.62; 95% CI, 0.29–1.30; P=0.21). Conclusion: Appropriate antibiotics included timing less than 60 min, spectrum and the dose was not significantly affected in 28-day mortality in emergency sepsis patients. Trial registration: The trial was retrospectively registered in the Thai Clinical Trial Registry, identification number TCTR20211216003.